Political Communication: Social Media Strengths and Threats in the 2019 General Election - Maharani, Prima Suci; Nurafifah, Nisma Laela (Political Science Program, Universitas Negeri Semarang, 2020)
Social media makes it easy for a group to exchange information and influence each other. Today, most Indonesians are familiar with social media and have social media accounts. Participating candidates in the 2019 General Election did not just ignore this, they used social media as a means to campaign. The candidates introduce their programs and try to get the sympathy of potential voters without having to go outside. It is more efficient in terms of time and cost. But apart from having a positive side, social media also has negative impacts such as the rise of hoaxes, post-truth and black campaigns. This study aims to examine the phenomenon of the widespread use of social media as a political campaign strategy by building a sense of sympathy and voter emotions rather than rationality. The author uses data collection methods with literature study, and the method used for this study is literature study.